Dos Irmãos Grimm a Câmara Cascudo: um caso de tradução cultural - Schefer, Maria Cristina (My University, 2014)
The verification of inter-quality of what is textual between Snow White and Red Small Hat from Grimm brothers and The Buried Girl Alive and The Girl of Gold Earrings from Câmara Cascudo, it gives indications of specific cultural translation of the Brazilian Northeast, which, yonder bringing up to date social archetypes and interdicts, it is adjusted to the Northeast Regionalistic Movement s objectives, idealized cultural project by Gilberto Freyre in 1926, in favor for the valorization of that region. A study based on Northeast Regionalistic Manifest makes possible the verification of the cultural translation daily practice, in the adaptation of the popular narratives, it is made first by usual men, in view of stories circulation space. Subsequent to this, but without needing the beginning as the second moment of the translation, it is found in the Luis da Câmara Cascudo s social work, follower of the Freyre s Movement, the intention to also become these narratives registers of the national patrimony, since they had been published in the entitled work Brazil s Traditional Stories, edited for the first time in 1946.
A verificação de intertextualidade entre os contos Branca de Neve e Chapeuzinho Vermelho , dos irmãos Grimm e A menina enterrada viva e A menina dos brincos de ouro , de Câmara Cascudo, dá indícios de uma tradução cultural específica do Nordeste brasileiro, a qual, além de atualizar arquétipos e interditos sociais, está adequada aos objetivos do Movimento Regionalista do Nordeste, projeto cultural idealizado por Gilberto Freyre em 1926, em prol da valorização daquela região. Um estudo, baseado no Manifesto Regionalista do Nordeste, possibilita a verificação da prática cotidiana de tradução cultural, na adaptação das narrativas populares, feita primeiramente por homens ordinários, dado o espaço de circulação dos contos. Posterior a isso, mas sem precisar o início do segundo momento da tradução, verifica-se, no trabalho do auctor social Luís da Câmara Cascudo, adepto do Movimento freyreano, a intenção de tornar essas narrativas também registros do patrimônio nacional, visto que elas foram publicadas na obra intitulada Contos tradicionais do Brasil, editada pela primeira vez em 1946.
Keywords: Literatura comparada; Tradução cultural; Intertextualidade; Contos populares; Homens ordinários; Autores sociais; Regionalidade; Folclore brasileiro; Literatura comparada; Luís da Câmara Cascudo; Cultural translation; Inter-quality of what is textual; Popular stories; The quality of what is regional; Social authors